Successful treatment of severe post hematopoietic stem cell transplantation bronchiolitis obliterans syndrome with lung transplantation in a patient with multi‐organ chronic graft‐versus‐host disease. Issue 9 (19th September 2022) - Pénichoux, Juliette; Bouclet, Florian; Alani, Mustafa; Contentin, Nathalie; Ménard, Anne‐Lise; Leprêtre, Stéphane; Lenain, Pascal; Stamatoullas, Aspasia; Lhuillier, Elodie; Lanic, Hélène; Lemasle, Emilie; Dubois, Sydney; et al.
Abstract: Allogeneic stem cell transplant and chronic graft‐versus‐host disease may lead to severe non‐infectious pulmonary disease in 6% of patients at 5 years. We report the case of a young patient with acute myeloid leukemia who successfully received bilateral lung transplantation for severe bronchiolitis obliterans syndrome. Abstract : Post‐allogeneic hematopoietic stem cell transplantation bronchiolitis obliterans syndrome severely affects the quality of life and prognosis of patients and may be successfully treated with bilateral lung transplantation in selected patients even in the presence of a multi‐organ chronic graft‐versus‐host disease, if controlled.